Implementing Intensive Interaction in schools : guidance for practitioners, managers and coordinators - Kellett, Mary (David Fulton, 2003)
"This book is for practitioners, coordinators and managers in schools using Intensive Interaction with pupils who have severe and complex learning difficulties. It addresses a range of challenges across special, inclusive and ever-changing contexts. It will also be of interest to those wanting to do further research and evaluation of Intensive Interaction and to teacher-educators."--Jacket